1-HALOGENO-5,6-EPOXY-6-METHYL-2-HEPTANOL, ITS DERIVATIVE AND PREPARATION THEREOF - MORITA YOSHIMI; TAKAYANAGI HISAO (1982)
NEW MATERIAL:A compound of formulaI(X is halogen; Y is H or a protecting group of the hydroxyl group). EXAMPLE:1-Chloro-5,6-epoxy-6-methyl-heptan-2-ol. USE:Useful as an important intermediate for the total synthesis of (1RS, 4SR, 5RS)-4-(4,8-dimethyl-5-hydroxy-7-nonenyl)-4-methyl-3,8-dioxabicyclo[3. 2.1]-octane- 1-acetic acid having the activity as a contraceptive agent. PROCESS:A 1-halogeno-6-methyl-5-hepten-2-ol of formula II or a reactive derivative thereof is epoxidized to give the compound of formulaI. m-Chloroperbenzoic acid, etc. may be used as the epoxidizing agent.